Tea consumption may improve psychological resilience among older adults with chronic diseases: a prospective cohort study - Chen, Huihe; Gao, Ming; Huang, Lanhui; Guan, Xuehai; Wei, Yuanfei (Frontiers in Psychiatry, 2025)
ObjectiveTo investigate the association between tea consumption and the dynamic change in psychological resilience (PR) among older adults with chronic diseases.Study designA prospective cohort study.MethodsA total of 26,454 adults aged 60 and older from the Chinese Longitudinal Healthy Longevity Study were analysed. Tea consumption and PR were evaluated through survey at baseline and at the 3-year follow-up using drinking frequency and a validated scoring scale. Clustering analysis was used to identify multimorbidity clusters. Multivariable analysis was employed to investigate the association between tea consumption and PR change. Several sensitivity analyses were conducted.ResultsThe sample had an average age of 85.6 ± 12.0 years, with 55.7% female. Ten distinct multimorbidity clusters were identified. Daily tea drinkers exhibited greater improvement in PR (OR=1.176, 95% CI: 1.043-1.327) compared to non-drinkers over a 3-year follow-up. Females (OR=1.362, 95% CI: 1.124-1.649) and participants in the younger-old group (age < 85 years, OR=1.243, 95% CI: 1.075-1.436) were more likely to experience this benefit. This positive association remained significant in participants with multimorbidity (OR=1.437, 95% CI: 1.116-1.850), but not in those considered robust (OR=1.102, 95% CI: 0.931-1.304) or with a single chronic disease (OR=1.117, 95% CI: 0.878-1.421). Specifically, this association was most pronounced within the multimorbidity cluster characterized by cardiometabolic conditions (OR=3.902, 95% CI: 1.081-14.084). The results remained consistent across numerous sensitivity analyses.ConclusionsDaily tea consumption is positively associated with PR improvement among older adults, particularly those with cardiometabolic multimorbidity. Promoting tea drinking habit may represent a viable strategy for promoting active health during late life stages.